THE EFFECT OF THE SPLIT NACA 0015 AIRFOIL ON VARIATIONS IN REYNOLDS NUMBER - Satria, Muhammad Fari; Julian, James; Wahyuni, Fitri; Iskandar, Waridho (TURBO [Tulisan Riset Berbasis Online], 2023)
This research will discuss the advantages of a NACA 0015 airfoil with a split configuration under varying Reynolds numbers. Computational Fluid Dynamics (CFD) simulations with a K-epsilon turbulence model were conducted on a two-dimensional split airfoil to achieve this goal. Initially, simulations were carried out for the unsplit airfoil geometry at different Reynolds numbers within an angle of attack (AoA) range of 00 to 250. Subsequently, simulations were performed for the split airfoil geometry at various Reynolds numbers within the same AoA range. The unsplit airfoil experiences stall at AoA greater than 110 degrees, while the split airfoil experiences stall at AoA greater than 130 degrees. Additionally, using a split airfoil enhances Cl, with an average increase of approximately 7-8% across different Reynolds numbers. In addition to the Cl improvement, the split airfoil exhibits lower Cd values than the unsplit airfoil, with an average reduction of about 26-28% across all Reynolds number variations. Overall, using separate airfoils improves the aerodynamic performance of the airfoil, with an average increase in Cl/Cd of approximately 33-37% across all Reynolds number variations. In conclusion, the split airfoil performs better than the unsplit airfoil.